2008
DOI: 10.1152/ajpregu.90346.2008
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent hypoxia has organ-specific effects on oxidative stress

Abstract: Obstructive sleep apnea is characterized by upper airway collapse, leading to intermittent hypoxia (IH). It has been postulated that IH-induced oxidative stress may contribute to several chronic diseases associated with obstructive sleep apnea. We hypothesize that IH induces systemic oxidative stress by upregulating NADPH oxidase, a superoxide-generating enzyme. NADPH oxidase is regulated by a cytosolic p47(phox) subunit, which becomes phosphorylated during enzyme activation. Male C57BL/6J mice were exposed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
69
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(82 citation statements)
references
References 96 publications
(99 reference statements)
9
69
1
3
Order By: Relevance
“…Furthermore, genetic interventions have been applied to rodents that can yield novel mechanistic insights. Experiments using knockout mice have demonstrated pathologic interactions between IH and nicotinamide adenine dinucleotide reduced oxidase (40), adipose angiopoietin-like 4 (41), and hypoxia-inducible factor-1a (42,43) in mediating downstream consequences of IH.…”
Section: Ihmentioning
confidence: 99%
“…Furthermore, genetic interventions have been applied to rodents that can yield novel mechanistic insights. Experiments using knockout mice have demonstrated pathologic interactions between IH and nicotinamide adenine dinucleotide reduced oxidase (40), adipose angiopoietin-like 4 (41), and hypoxia-inducible factor-1a (42,43) in mediating downstream consequences of IH.…”
Section: Ihmentioning
confidence: 99%
“…Endothelial dysfunction has been related to the progression of hypertension in OSA patients and animals exposed to intermittent hypoxia due to the increased plasmatic levels of proinflammatory cytokines (Biltagi et al, 2008, Jelic et al, 2008, Jun et al, 2008, Tam et al, 2007, Williams & Scharf, 2007. It is likely that an increased production of ROS induced by the hypoxia-reoxygention cycles may evoke the expression of genes and the synthesis of proinflammatory cytokines, mediated by the activation of transcription factors such as the nuclear factor kappa B (NF-κB), the activator protein 1 and HIF-1 (Semenza & Prahbakar, 2007).…”
Section: Pro-inflammatory Cytokinesmentioning
confidence: 99%
“…Possible explanations could be that though serum ALT and AST are considered as desirable non-invasive biomarkers of NAFLD, they are neither sensitive nor specific to diagnose NAFLD and characterize its severity. [34] Also, Jun et al [35] demonstrated that lipid peroxidation is increased in the liver due to CIH in animal modal of OSA, but serum aminotransferases remained within the normal range suggesting the possibility that histopathological changes in the liver are not always associated with a concomitant increase in biochemical markers. Moreover the NASH clinical research network currently recommends serum ferritin to identify NAFLD patients at risk for NASH than serum aminotransferases.…”
Section: Discussionmentioning
confidence: 99%